2021
DOI: 10.1016/j.mayocp.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Unruptured Intracranial Aneurysms and Aneurysmal Subarachnoid Hemorrhage

Abstract: Unruptured intracranial aneurysms (UIAs) are commonly acquired vascular lesions that form an outpouching of the arterial wall due to wall thinning. The prevalence of UIAs in the general population is 3.2%. In contrast, an intracranial aneurysm may be manifested after rupture with classic presentation of a thunderclap headache suggesting aneurysmal subarachnoid hemorrhage (SAH). Previous consensus suggests that although small intracranial aneurysms (<7 mm) are less susceptible to rupture, aneurysms larger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 233 publications
(292 reference statements)
1
88
0
4
Order By: Relevance
“…Flemming et al (12) studied the natural history of vertebrobasilar non-saccular aneurysms and found that the mortality and morbidity were 40 and 53% during the follow-up, respectively, with the median survival of 7.8 years. Due to the high risk of rupture and poor natural history of VBTLAs, once detected, it is important to individualize surgical intervention on the basis of the overall medical condition of the patient (1,(11)(12)(13). For patients with aneurysmal subarachnoid hemorrhage, aneurysm obliteration should be performed as soon as the patient is medically stabilized because of rebleeding (1,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flemming et al (12) studied the natural history of vertebrobasilar non-saccular aneurysms and found that the mortality and morbidity were 40 and 53% during the follow-up, respectively, with the median survival of 7.8 years. Due to the high risk of rupture and poor natural history of VBTLAs, once detected, it is important to individualize surgical intervention on the basis of the overall medical condition of the patient (1,(11)(12)(13). For patients with aneurysmal subarachnoid hemorrhage, aneurysm obliteration should be performed as soon as the patient is medically stabilized because of rebleeding (1,13).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high risk of rupture and poor natural history of VBTLAs, once detected, it is important to individualize surgical intervention on the basis of the overall medical condition of the patient (1,(11)(12)(13). For patients with aneurysmal subarachnoid hemorrhage, aneurysm obliteration should be performed as soon as the patient is medically stabilized because of rebleeding (1,13). In this study, the 5-year complication-free and overall cumulative survival rates were 82.0 and 89.8%, respectively, which indicated that the surgical intervention could benefit patients with vertebrobasilar aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Moreover, survivors of SAH are often accompanied by multiple neurological deficits that severely affect patients' ability to work and their quality of life. 2,3 Existing treatments for SAH remain unsatisfactory. Recently, hydrogen sulfide (H 2 S), the third gaseous signaling molecule, has been found to play an important role in physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The four broad types of aneurysms are saccular, fusiform, dissecting, and mycotic, of which saccular (or berry) aneurysms are the most common, accounting for around 90% [2]. The prevalence of intracranial aneurysms in the general population is approximately 3.2%, though most are asymptomatic [3][4][5]. Berry aneurysms are most commonly located in the anterior circulation, at the junction between the anterior communicating artery (ACOM) and the anterior cerebral artery (ACA), the bifurcation of the middle cerebral artery (MCA), and the junction between the posterior communicating artery (PCOM) and the internal carotid artery (ICA) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%